CsrA coordinates the expression of ribosome hibernation and anti-σ factor proteins - Christine Pourciau; Helen Yakhnin; Archanna Pannuri; Mark G. Gorelik; Ying-Jung Lai; Tony Romeo; Paul Babitzke (mBio, 2023)
ABSTRACTBacterial growth rate varies due to changing physiological signals and is fundamentally dependent on protein synthesis. Consequently, cells alter their transcription and translation machinery to optimize the capacity for protein production under varying conditions and growth rates. Our findings demonstrate that the post-transcriptional regulator CsrA in Escherichia coli controls the expression of genes that participate in these processes. During exponential growth, CsrA represses the expression of proteins that alter or inhibit RNA polymerase (RNAP) and ribosome activity, including the ribosome hibernation factors RMF, RaiA, YqjD, ElaB, YgaM, and SRA, as well as the anti-σ70 factor, Rsd. Upon entry into the stationary phase, RaiA, YqjD, ElaB, and SRA expression was derepressed and that of RMF, YgaM, and Rsd was activated in the presence of CsrA. This pattern of gene expression likely supports global protein expression during active growth and helps limit protein production to a basal level when nutrients are limited. In addition, we identified genes encoding the paralogous C-tail anchored inner membrane proteins YqjD and ElaB as robust, direct targets of CsrA-mediated translational repression. These proteins bind ribosomes and mediate their localization to the inner cell membrane, impacting a variety of processes including protein expression and membrane integrity. Previous studies found that YqjD overexpression inhibits cell growth, suggesting that appropriate regulation of YqjD expression might play a key role in cell viability. CsrA-mediated regulation of yqjD and ribosome hibernation factors reveals a new role for CsrA in appropriating cellular resources for optimum growth under varying conditions.IMPORTANCEThe Csr/Rsm system (carbon storage regulator or repressor of stationary phase metabolites) is a global post-transcriptional regulatory system that coordinates and responds to environmental cues and signals, facilitating the transition between active growth and stationary phase. Another key determinant of bacterial lifestyle decisions is the management of the cellular gene expression machinery. Here, we investigate the connection between these two processes in Escherichia coli. Disrupted regulation of the transcription and translation machinery impacts many cellular functions, including gene expression, growth, fitness, and stress resistance. Elucidating the role of the Csr system in controlling the activity of RNAP and ribosomes advances our understanding of mechanisms controlling bacterial growth. A more complete understanding of these processes could lead to the improvement of therapeutic strategies for recalcitrant infections.